Interações comunicacionais em Itabira em função da expectativa de dois acontecimentos : a exaustão das minas de minério de ferro e o rompimento de barragens de rejeitos - Marlene Pereira Machado (2023)
This research seeks to understand the expectation of two events in the city of Itabira, located 105 kilometers from Belo Horizonte (MG), Minas Gerais, Brazil: the exhaustion of iron ore mines and the possibility of rupture of tailing dams. The expectation of those events, which are part of the dimension of becoming, changed the routine of the municipality, which now lives the perspective of risk: risk of iron ore being exhausted, putting an end to the its main economic activity; and one of its dams bursting, causing incalculable damage. Those are events that have not yet occurred, but the expectation of those possible events modifies the ways of life and sociability in the municipality. The imminence of the depletion of the mines and the possibility of dam rupture are present in the routine of the city and require learning to live with those conflicts that strain the relationship between the mining company, Vale, the government, institutions and society. The research aimed to understand the collective experience that takes place in the locality in function of the expectation of the two events. The study has as theoretical basis the event, audiences and experience, seeking to correlate the notions of event and expectation in the process of formation and movement of the audiences in the place. The main guiding hypothesis is that it is not only an event in itself, that happened or that happens, that causes audiences to form and move, but also events that did not happen and whose expectations call for action and public discussion. That is, the impact of the expectation of those future events, imminent or just possible, already occurs in the present, affecting the subjects. The research undertaken is of qualitative basis and carried out in a constructive way, considering that it is working with events in process. It involved research of the main references related to the theme of documentary research, in order to follow the recent history of Itabira and its imbrication with the mineral industry, knowing the context in which both expectations emerged; extensive monitoring of the media and systematic observation of the routine of the city, to show the potential of the reverberation of the expectation of the two events in the life of the Itabirans and semi-structured individual interviews fundamental to know the impacts on the subjects and the collective experience that emerges there, from the perception of the risks and the attitude of readiness that these situations require. In addition to contributing to the theoretical and empirical advancement of studies on the audiences and its forms of mobilization and to the understanding of their vulnerabilities, it can also offer subsidies for a better understanding of processes related to the closure of mines, which tend to increase in Brazil and in the world due to the projections of institutions and specialists linked to the mineral sector, if under study, composing a theoretical framework to illuminate empiricism; and for issues related to the safety of populations in the face of the possibilities of rupture of tailing dams, fundamental after the recent disasters that occurred in Brazil. The research made it possible to understand that expectations are fluctuating and sometimes low, sometimes high, intense or mild, from the behavior of the media, from the chained events that are effectively carried out, from the action of audiences and social actors that are organized in the present, carrying the senses of risk and readiness that mark the collective experience in the territory. They open up to the idea that an expectation never comes alone. When it emerges, it creates and feeds other expectations, which are updated according to the prominent events, the context, and the potential of the outcome to affect the subjects.